GREEN SUPPLY CHAIN MANAGEMENT AS DRIVERS OF SUSTAINABLE PERFORMANCE: A STUDY OF SMES IN EAST JAVA - Surachman; Siti Aisjah (CV. Radja Publika, 2024)
This research used a survey technique to investigate the beneficial impact of green supply chain management methods on the economic performance of SMEs in East Java. The study examines the exemplary leaders and managers of MSMEs. We conduct sampling using the purposive sampling approach. The structural equation modeling (SEM) method is used as the data analysis tool. The study results indicate that green buying positively influences investment recovery and improves the performance of SMEs. Likewise, Eco-Design demonstrates a positive influence on investment recovery, hence augmenting its effect on the performance of SMEs. Moreover, investment recovery improves the performance of SMEs by maximizing asset usage and operational efficiency. This study underscores the beneficial effects of green buying and eco-design on the economic performance of SMEs, demonstrating their potential to provide higher investment returns and improved operational efficiency. Investment recovery serves as a mediating variable between sustainable practices and corporate results, highlighting the possibility for development and success in this domain.